Analysis of the Effectiveness of Contribution of Rural and Urban Land and Building Taxes to Increasing Original Local Government Revenue - M. Harry Mulya Zein (International Forum of Researchers and Lecturers, 2023)
This study aims to analyse the effectiveness and contribution of rural and urban land and building taxes to the original local government revenue in Purwakarta Regency during 2016-2019. The method used in this study is a descriptive method using secondary data sources in the form of reports on the realisation of Rural and Urban Land and Building Taxes and Original Local Government Revenue of Purwakarta Regency. Analysis techniques include measuring the effectiveness and contribution of Rural and Urban Land and Building Taxes to Original Local Government Revenue. The results showed fluctuations in the receipt of Rural and Urban Land and Building Taxes during the study period. 2019 recorded the lowest effectiveness, while 2017 showed significant improvement. The average efficacy of Rural and Urban Land and Building Taxes during the period was satisfactory. However, the contribution of Rural and Urban Land and Building Taxes to Original Local Government Revenue showed greater variation, with some years recording relatively low contributions. This indicates the need for increased consistency and efficiency in the tax collection system and improved services to taxpayers.